Pharmacokinetics and plasma concentration of thiopental in normal and stressed chickens with hydrogen peroxide - MOUSA, Y.J.; AMIN, S.M.; SHAABAN, KH.A. (Journal of the Hellenic Veterinary Medical Society, 2021)
No previous study deals with hydrogen peroxide (H2O2)-induced oxidative stress (OS) and its influence on thiopental anesthesia, its plasma concentration and pharmacokinetic profile in 7-14 day old chickens. OS induction was made by the daily supply of H2O2 from day one to the completion of the experiments on day 14th of chickens’ age. Median Effective Doses (ED50s) of hypnosis and analgesia were revealed an increase in thiopental efficacy by 7 and 18%, respectively in the stressed chickens in comparison to the normal one. Thiopental plasma concentration was analyzed at time 0.5, 1, 2, 4 and 24 hours after its injection at 35 mg/kg, IP to be 91.42, 54.35, 38.27, 22.30 and 7.51 μg/ml in the normal chickens and increased significantly by 74, 84, 48, 85 and 82% to be 159.01, 100.06, 56.71, 41.30 and 13.63 μg/ml in the stressed chickens, respectively. Thiopental pharmacokinetics parameters, which included Area Under the plasma Concentration (AUC0-∞), Area Under the Moment Curve (AUMC0-∞), Mean Residence Time (MRT) and elimination half-life (t1/2β) were increased in the stressed chickens by 82, 94, 6 and 8%, as well as, Clearance (Cl), elimination rate constant (Kel), and Steady-State Volume of Distribution (Vss) were decreased in the same group by 33, 14 and 41%, respectively. The results of this trial concluded that OS status intensifies thiopental anesthetic action mainly by increasing its plasma concentration and altering the pharmacokinetics profile, suggesting veterinarians to bear in mind when preparing the dose of thiopental to be given to stressed animals.